Prevalence and Mean Intensity of Anisakidae Parasite in Seafood Caught in the Mediterranean Sea Focusing on Fish Species at Risk of Being Raw-consumed. A Meta Analysis and Systematic Review. Issue 9 (3rd July 2016) - Colombo, Fabio; Cattaneo, Patrizia; Castelletti, Maddalena; Bernardi, Cristian
Abstract : Objective : To assess the prevalence and mean intensity of anisakids in seafood caught in the Mediterranean Sea, focusing on fish species at risk of being raw-consumed. Design : Systematic review and meta-analysis of studies published from 1960–2012. Study selection : Main criteria for the inclusion of studies were as follows: Findings of anisakid larvae, in both muscles and viscera; fish species for human consumption caught in the Mediterranean Sea; prevalence and mean intensity data for each species; and sample size equal to or more than 40 fishes. Results : Twelve studies were identified. Among these, four studies considered the following three fish species that are often consumed raw or preserved lightly, or not cooked thoroughly: anchovy, pilchard, and Atlantic mackerel. Data synthesis : All pooled analyses were based on the random-effect model. Anisakids prevalence in fish muscle was 0.64% ( P < 0.0001), in viscera it was 1.34% ( P < 0.0001), and overall prevalence was 0.95% ( P < 0.0001). Mean intensity in muscle was 2.31 ( P = 0.0083), in viscera it was 1.55 ( P = 0.0174), and overall it was 1.81 ( P < 0.0005). Heterogeneity indices (I 2 ) were significantly high with the exception of viscera mean intensity. Conclusions : Anchovy, pilchard, and Atlantic mackerel have a low prevalence and mean intensity of anisakidae larvae in both viscera and muscles. Mean Intensity was also low.